Calculation method of the bearing capacity of a novel modular joint of an aluminium alloy lattice shell structure. (December 2021) - Zhao, Caiqi; Zhou, Yunwen; Wang, Gang; Li, Haoyue; Wang, Yating
Abstract: This paper proposes the use of a novel modular joint to overcome the shortcomings of existing aluminium alloy gusset joints. Bearing capacity tests are performed on the bearing capacity of four sets of joints in the early stage, and the force characteristics and failure mechanism of the novel modular joint are summarized. On this basis, this study conducts theoretical research on the design method of this new type of joint. According to the four failure modes that occurred in the experiment, namely, the bending failure of the aluminium alloy beam, the shear failure of the bolt group, the tensile and shear failure of the modular unit, and the local buckling failure of the unit bottom plate, a formula for calculating the ultimate bearing capacity of each component is provided. According to the working mechanism of modular joints, theoretical formulas for the ultimate flexural bearing capacity and initial stiffness of the joints are derived according to the three-part bending moments produced by each component. Based on a power function model, a prediction formula is fitted to the bending moment-rotation curve of the new joint and compared with the measured values of the joint and 22 numerical models. The results show that the average errors of the two sets of theoretical formulas are only 2.85% and 4.5%, fully verifying their validity and reliability. The results provide a theoretical basis for the engineering design and application of this type of joint.